Effect of high-moisture extrusion and addition of transglutaminase on major peanut allergens content extracted by three step sequential method. (15th August 2022) - Faisal, Shah; Zhang, Jinchuang; Meng, Shi; Shi, Aimin; Li, Liu; Wang, Qiang; Maleki, Soheila J.; Adhikari, Benu
Highlights: HME processing significantly reduced all the major peanut allergens level. HME processing alone or with TGase significantly reduced the IgE binding. Improvised 3 stages protein extraction significantly improved the extractable proteins. HME with lower TGase, significantly enhanced fibrous textured formation. Abstract: The effect of high-moisture extrusion (HME) with or without transglutaminase (TGase) on peanut allergen levels and their extractability was studied. A three-stage sequential protein extraction significantly improved the protein recovery in processed samples (extrudate meat analogue); from 5.56 to 18.75 mg/100 mg without TGase, and from 4.59 to 20.82 mg/100 mg with 0.3% TGase. The total major allergen content was reduced by 91% (Ara h 1), 61% (Ara h 2), 60% (Ara h 6), and 55% (Ara h 3). Western-blot analysis of soluble extracts reflected the presence of Ara h 1 and Ara h 2 in significantly lower, indicating a potential reduction in IgE binding. During different processing zones, the most significant reduction in allergenic proteins was in the melting zone. The significant alteration in secondary and tertiary structures as a result of crosslinking shearing and degradation of proteins is likely to lead to allergen reduction.